The prevention and treatment of opportunistic infections in HIV-infected adults - G. Maartens (South African Family Practice)
A number of lengthy and comprehensive articles and guidelines exist with regard to the treatment and prevention of opportunistic infections, but this guidelines is designed to be easy and simple for a practitioner to use. It is presented in a simplified format. The guideline is supported by evidence-based studies and adapted to be appropriate to the local situation. It should be noted that the only drugs that are licensed in South Africa have been recommended and in addition, at all times the most cost-effective regimen(s) have been endorsed. Alternative regimen(s) have been listed where appropriate but these are not exhaustive. A practitioner dealing with more complex problems may find it necessary to consult with a colleague or refer to more comprehensive material.